Determination of Relationship among Macronutrient Intake and Overweight/Obesity in School Children from Celaya, Guanajuato, Mexico - Flores-Vargas, Gilberto; Padilla-Raygoza, Nicolás; Gallardo-Luna, María de Jesús; Navarro-Olivos, Efraín; Urrusquieta-Flores, Hazel Marisol; Jimenez-García, Sandra Neli; Ramírez-Moreno, Esther; Benítez-Guerrero, Verónica; Arias-Rico, José (Issues and Development in Health Research Vol. 2, 2021)
Objective: To determine if exists relationship between macronutrient intake and overweight/obesity in schoolchildren, from Celaya, Guanajuato, Mexico. Methods: 225 school-aged children (6 to 13 years) were evaluated in Celaya, Guanajuato. Anthropometric measurements were performed and individual interviews with parents and children were conducted to collect information on the frequency of food consumption using a validated questionnaire (SNUT) from which the intake of macronutrients (carbohydrates, proteins, and fats) and fat subtypes. Chi squared statistic was computed, and its corresponding p-value, to identify the association of macronutrient intake with overweight/obesity in schoolchildren. Results: There are not relationship between macronutrient intake (proteins, carbohydrates, and lipids) and overweight/obesity in this sample of schoolchildren from Celaya, Guanajuato. Macronutrients with obesity were: carbohydrates with obesity, X2 = 3.47, P=.18; proteins X2 = 3.36, P=.19; lipids (Z for two proportions) with P>.05. Conclusion: It is possible that there are other strong factors in relationship with overweight/obesity, such as physical activity.